COLOURED STICK: TEACHING WITH A COMPREHENSIVE GAME FOR IMPROVING CHILDREN’S SOCIAL-EMOTIONAL ABILITY IN KINDERGARTEN - Sri Tatminingsih (Különleges Bánásmód, 2019)
The emotional ability must be properly managed in order to survive and adapt to social life so that social and emotional abilities can be trained from an early age. As a part of early childhood, kindergarten is one of the most effective places to help children develop social and emotional abilities effectively through play activities. Thus, kindergarten teachers need to find alternative activities and play equipment that can stimulate socio-emotional abilities. One way is by means of the game "Coloured Stick" made of pieces of wood that are developed by combining three types of games, namely constructive games, educational games, and traditional games. This teaching tool can be applied in an integrated manner in kindergarten learning activities, which include the opening, core, and cover with a strategy that varies according to the indicators of social-emotional development.  The learning process is the use of the game "Coloured Stick" which is systematically designed and integrated so as to facilitate its application. The application of this tool was tested in small groups of 8 students over eight meetings in July and August 2015, and a large group of 14 students over 12 meetings in August and September 2015 in Fithria Islamic Kindergarten, South Jakarta. Subjects in the test groups were teachers and kindergarten students.  The results of both the trial groups were seen from the difference between initial and final assessments. The small trial group results increased by 0.1 points (4.88%) up to 0.29 points (9.76%) whereas the large trial group results increased by 0.05 points (1.63%)to 0.93 points (30.83%). Descriptive this increase occurred in the child are varied and each child's progress in socio-emotional capabilities in the grain or indicators of social-emotional abilities are different. This is very possible because each child has a differing ability to absorb the learning content. The results show that the colored sticks game tool can help children develop social skills because the learning process can be carried out in groups. In addition to boosting the child's emotional development, it can also help children develop confidence and respect for themselves, not become easily frustrated because the concepts are according to the age and development of the children, and to exercise patience because they have to wait for their turn to play.